Improving IT Governance Maturity at Universitas Sebelas Maret Using COBIT 2019 - Setyawan, Haidar Hendri; Khadija, Mutiara Auliya; Budianto, Aris (Journal of Information System and Informatics, 2025)
This study evaluates and improves the IT governance maturity of the Directorate of ICT at Universitas Sebelas Maret using the COBIT 2019 framework. The evaluation was driven by increasing IT complexity, resource inefficiencies, and low risk management capability. A case study approach applied COBIT 2019 domains to assess practices and identify gaps, with data gathered through interviews, observations, and document analysis. Significant deficiencies were found in six key processes. The highest gap score is APO12 (Managed Risk) at 1.89, followed by DSS04 (Managed Continuity) at 1.88, DSS01 (Managed Operations) at 1.75, APO14 (Managed Data) at 1.74, DSS05 (Managed Security) at 1.57, and the lowest is APO01 (Managed I&T Framework) at 1.27, with all domains targeting a maturity level of 3. Results indicate current maturity scores fall below expectations, highlighting the need for systematic improvement. A phased strategic plan was developed for short, medium, and long-term priorities, aligned with resources and organizational needs. The study demonstrates that structured implementation of COBIT 2019 can enhance governance alignment, improve risk control, and ensure sustainable ICT performance, providing a roadmap for future IT governance at the university.